Implementasi Program Keluarga Harapan (PKH) dalam Upaya Meningkatkan Kesejahteraan Masyarakat (Studi Desa Lasori, Mawasangka Timur, Buton Tengah) (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2022)
This thesis is the result of research that describes how much influence Implementasi Program Keluarga Harapan (PKH) Dalam Upaya Meningkatkan Kesejahteraan Masyarakat di Desa Lasori, Kecamatan Mawasangka Timur Kabupaten Buton Tengah. The purpose of this study was to determine the implementation and impact of the family of hope program in an effort to improve the welfare of the community as well as the supporting and inhibiting factors. The sampling technique used was purposive sampling, with data from 1 village head, 1 Pkh officer and 7 Pkh recipient communities. The data collection method used in this research is triangulation, the data analysis is qualitative. The data analysis technique was carried out by collecting data, reducing data and identifying and categorizing. Where the results of PKH aid receipts with the amount of assistance in the education sector as much as 4,400,000 / year which is accumulated from the elementary education level worth 900,000 / year, junior high school worth 1,500,000 / year and high school worth 2,000,000 / year. Then the amount of assistance in the health sector is 6,000,000/year with details for pregnant women and toddlers each as much as 3,000,000/year. As well as the amount of assistance in the social welfare sector as much as 4,800,000/year consisting of the elderly group worth 2,400,000/year and the disabled group worth 2,400,000/year.